2010
DOI: 10.1007/s10439-010-9902-z
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid Mechanics of Special Organs and the Issue of System Control

Abstract: In the field of fluid flow within the human body, blood flow in the systemic circulation has been the main focus since the recognition by William Harvey that blood was in fact in continuous circulation and carried by a network of blood vessels. But beyond the systemic circulation, other fluids and other fluid flow phenomena pervade the body so totally that it would be hard to imagine a bodily function of any kind that does not involve fluids or fluid flow. In fact, the study of the systemic circulation is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Mechanical stimulation due to interstitial fluid flow or slowly moving convective flow through the tissue interstitium has emerged as a potent mediator of vascular morphogenesis . The driving forces for interstitial flow are hydrostatic and osmotic pressure differences between blood vessels, the interstitial space, and lymphatic vessels (Figure ). These forces (also known as the Starling forces ) determine the rate of transendothelial filtration (Figure ).…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stimulation due to interstitial fluid flow or slowly moving convective flow through the tissue interstitium has emerged as a potent mediator of vascular morphogenesis . The driving forces for interstitial flow are hydrostatic and osmotic pressure differences between blood vessels, the interstitial space, and lymphatic vessels (Figure ). These forces (also known as the Starling forces ) determine the rate of transendothelial filtration (Figure ).…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%
“…The level of transvascular volume flux (J v ) scales with the hydraulic conductivity (L p ), which is a function of vessel permeability. Fluid outside of blood vessels moves through the interstitium as interstitial flow that is collected by lymphatic vessels lymphatic vessels 55,56 (Figure 3). These forces (also known as the Starling forces 57 ) determine the rate of transendothelial filtration ( Figure 3).…”
Section: Lymphatic Vessel Mechanobiologymentioning
confidence: 99%
“…This adhesion may have resulted from surface tension or direct adhesion. We have shown that these vessels show significant expression of integrin components necessary for adhesion to collagen 27 , 28 .While we are uncertain of the exact adhesion mechanism, the results do clearly illustrate that external tethering facilitates the suction effect in the presence of negative transmural pressures.…”
Section: Discussionmentioning
confidence: 68%
“…The study of modeling for surfactant transport is important in technological applications as well as biological/clinical aspects. Pulmonary surfactant plays a vital role in reducing the surface tension of the liquid lining alveoli and airways, and significantly influences the behavior of the liquid in lung [4][5][6].…”
Section: Introductionmentioning
confidence: 99%